The Effect of TiO2 Nanoparticles on The Performance of Kappaphycus Alvarezii Biopolymer for Enhanced Oil Recovery - Muhammad Taufiq Fathaddin; Onnie Ridaliani Prapansya; Pri Agung Rakhmanto; Dwi Atty Mardiana; Wydhea Ayu Septianingrum; Sonny Irawan; Ridho Abdillah (Testing Center for Oil and Gas LEMIGAS, 2025)
This study investigates the performance of a novel, environmentally friendly nanocomposite, utilizing the natural biopolymer Kappaphycus alvarezii enhanced with TiO2 nanoparticles, for Enhanced Oil Recovery (EOR) via polymer flooding. The application of this nanocomposite was aimed to simultaneously enhance microscopic displacement and macroscopic sweep efficiency. The research method used was laboratory testing which included solution stability, viscosity, interfacial tension (IFT), and rock wettability tests in various polymer concentrations (2,000–6,000 ppm), TiO₂ (2,000–4,000 ppm), and salinity (6,000–30,000 ppm) at temperatures of 30–80°C. Quantitative laboratory results confirm fluid property improvements: TiO2 addition increased the solution viscosity by up to 11 cP where an average increase up to 7.11% in high-salinity brines, reduced the Interfacial Tension (IFT) from 7.54 dyne/cm to 6.80 dyne/cm (a 9.8% reduction), and decreased the contact angle from 39.05° to 28.51°, confirming enhanced water-wetness. Core flooding experiments demonstrated that the polymer flooding yielded an incremental oil recovery factor after waterflooding ranging from 6.67% to 27.67%. The maximum total oil recovery achieved was 69.17% at the optimal concentration of Polymer 4,000 ppm and TiO2 2,000 ppm. These specific findings highlight the significant potential of the Kappaphycus alvarezii–TiO2 nanocomposite as an effective EOR agent.